The The Impact of Climate Change on Human Health in Khyber Pakhtunkhwa (KPK) Pakistan: A Literature Review (2015-2025) - Atta Ur Rahman; Inayat Ur Rahman; Muhammad Raza; Sahib Bahadar (Tecno Scientifica Publishing, 2026)
Climate change is a pressing global issue with significant implications for human health, especially in vulnerable regions such as Khyber Pakhtunkhwa, where environmental and socio-economic challenges amplify health risks. Climate variability has been linked to an increasing burden of communicable and non-communicable diseases, highlighting the need for a comprehensive literature review. This article reviews studies published between 2015 and 2025 on the health impacts of climate change in Khyber Pakhtunkhwa. The search strategy included major databases, namely PubMed, Google Scholar, Scopus, Web of Science, ScienceDirect, and SpringerLink, using the keywords “climate change,” “human health,” and “KPK.” Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 1,153 papers were initially identified, of which 55 met the inclusion criteria and were selected for in-depth analysis. The findings revealed several climatic factors affecting health, including extreme temperatures (38 studies), precipitation variability (29 studies), humidity (22 studies), and flooding (15 studies). Most studies focused on the increasing burden of vector-borne diseases, particularly dengue and malaria, as well as respiratory diseases, water-borne diseases, and heat-related health outcomes associated with climate variability.